Choice of healthcare provider following reform in Vietnam - Lindholm Lars; Lofgren Curt; Thuan Nguyen; Chuc Nguyen (BMC, 2008)
Abstract Background In Vietnam, the health-sector reforms since 1989 have lead to a rapid increase in out-of-pocket expenses. This paper examines the choice of medical provider and household healthcare expenditure for different providers in a rural district of Vietnam following healthcare reform. Methods The study consisted of twelve monthly follow-up interviews of 621 randomly selected households. The households are part of the FilaBavi project sample - Health System Research Project. The heads of household were interviewed at monthly intervals from July 2001 to June 2002. Results The use of private health providers and self-treatment are quite common for both episodes (60% and 23% of all illness episodes) and expenditure (60% and 12.8% of healthcare expenditure) The poor tend to use self-treatment more frequently than wealthier members of the community (31% vs. 14.5% of illness episodes respectively). All patients in this study often use private services before public ones. The poor use less public care and less care at higher levels than the rich do (8% vs.13% of total illness episodes, which decomposes into 3% vs. 7% at district level, and 1% vs. 3% at the provincial or central level, respectively). The education of the patients significantly affects healthcare decisions. Those with higher education tend to choose healthcare providers rather than self-treatment. Women tend to use drugs or healthcare services more often than men do. Patients in two highest quintiles use health services more than in the lowest quintile. Moreover, seriously ill patients frequently use more drugs, healthcare services, public care than those with less severe illness. Conclusion The results are useful for policy makers and healthcare professionals to (i) formulate healthcare policies-of foremost importance are methods used to reduce self-treatment and no treatment; (ii) the management of private practices and maintaining public healthcare providers at all levels, particularly at the basic levels (district, commune) where the poor more easily can access healthcare services, is also important, as is the management of private practices and (iii) provide a background for further studies on both short and long-term health service strategies.